Pengembangan Modul Supervisi Bagi Pengawas SMK Kabupaten Situbondo - Fuad Hasan; Wawan Juandi; Umi Khoiriyah (Program Pascasarjana Universitas Ibrahimy, 2018)
This study aims to produce a product in the form of a coaching module for supervisors of SMK in Situbondo Regency. This module developed from the school supervisor's workbook that was published by the development center of education personal of human resource development, education quality assurance the Ministry of Education and Culture of Indonesia in 2015. The development was carried out on the discussion of SMK relation with business world and industry world. The development of this module is supplemented with supervision support instruments as a supervisory guide in conducted monitoring, evaluation of SMK activities program involving business world, and industry world. Product validation test of this research is conducted by material experts, linguists and supervisors as product users. The validation results of materials, experts and users if converted on a Likert scale, a scale of 5 indicates that were good qualification, achievement level (%) 75 - 89 revisions as necessary.